2017
DOI: 10.1186/s12894-016-0191-1
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent catheterisation with hydrophilic and non-hydrophilic urinary catheters: systematic literature review and meta-analyses

Abstract: BackgroundIntermittent catheterisation is the method of choice for the management of bladder dysfunctions. Different urinary catheters are available, but there is conflicting evidence on which type of catheter is best. The present study provides an objective evaluation of the clinical effectiveness of different subsets of urinary catheters.MethodsA systematic literature review was performed for published RCTs regarding hydrophilic coated and PVC (standard) catheters for intermittent catheterisation. Separate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 43 publications
(65 reference statements)
0
48
0
6
Order By: Relevance
“…Czerwonka et al [11] reported that high hydrophobicity of the P. mirabilis cell surface correlated with low biofilm amount, which is important for hydrophobic surfaces like glass. It was proved that hydrophilic catheters may prevent catheter-associated UTIs [47], so it would be advisable to evaluate hydrophobicity rates that are characteristic for the majority of P. mirabilis clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…Czerwonka et al [11] reported that high hydrophobicity of the P. mirabilis cell surface correlated with low biofilm amount, which is important for hydrophobic surfaces like glass. It was proved that hydrophilic catheters may prevent catheter-associated UTIs [47], so it would be advisable to evaluate hydrophobicity rates that are characteristic for the majority of P. mirabilis clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in 1972 by Lapides [130], catheter models and characteristics have significantly improved and today there is a wide selection of high-tech catheters available, covering the needs of nearly every patient. More recent data and expert panels are in favor of single-use catheters with a hydrophilic coating [131,132]. However, further evidence from prospective randomized controlled trials evaluating catheter type (coated vs. uncoated) and catheterization technique (sterile vs. clean vs. aseptic; single-use vs. re-use) in a broader context, including evaluation of therapy compliance, QoL, and costs is needed.…”
Section: Intermittent Self-catheterizationmentioning
confidence: 99%
“…Synthetic tapes are up-to-date rarely investigated in male neurological patients. Currently, only one small study presents promising data from a mixed adult and pediatric male neurological population treated with the AdVance sling [84]. RCT and data on long-term follow-up are lacking.…”
Section: Suspension Therapymentioning
confidence: 99%
“…expression was also found to be elevated in NDO patients [83,84]. Again, treatment with resiniferatoxin or BoNT/A intradetrusor injections was able to reduce TRPV1 expression in those patients responding also clinically to treatment [79,83,84] Despite their promising effects in human studies, the evidence for intravesical treatment with vanilloids such as capsaicin and resiniferatoxin is still very limited and adverse events including pelvic pain, facial flush, worsening of incontinence, autonomic dysreflexia, urinary tract infection, and haematuria are very frequent [85]. Intravesical vanilloids are not approved for treatment in LUTD / LUTS and have largely fallen into oblivion, particularly after the propagation of BoNT/A intradetrusor injections.…”
mentioning
confidence: 99%
See 1 more Smart Citation